2021
DOI: 10.3389/fmed.2021.595773
|View full text |Cite
|
Sign up to set email alerts
|

Early Viral Clearance and Antibody Kinetics of COVID-19 Among Asymptomatic Carriers

Abstract: Asymptomatic carriers contribute to the spread of Coronavirus Disease 2019 (COVID-19), but their clinical characteristics, viral kinetics, and antibody responses remain unclear. A total of 56 COVID-19 patients without symptoms at admission and 19 age-matched symptomatic patients were enrolled. RNA of SARS-CoV-2 was tested using transcriptase quantitative PCR, and the total antibodies (Ab), IgG, IgA, and IgM against the SARS-CoV-2 were tested using Chemiluminescence Microparticle Immuno Assay. Among 56 patients… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 19 publications
3
21
0
1
Order By: Relevance
“…Young COVID-19 patients are known to be mainly asymptomatic or pauci-symptomatic [ 7 , 31 ]. Children may act as hidden drivers of the pandemic, although schools were found not to be a high risk setting for transmission of SARS-CoV-2 during the first and second wave of infections and several studies found that school closures did not contribute to the control of the epidemic [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young COVID-19 patients are known to be mainly asymptomatic or pauci-symptomatic [ 7 , 31 ]. Children may act as hidden drivers of the pandemic, although schools were found not to be a high risk setting for transmission of SARS-CoV-2 during the first and second wave of infections and several studies found that school closures did not contribute to the control of the epidemic [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Real-time RT-PCR is considered the reference standard for SARS-CoV-2 detection with lower cycle threshold (Ct) values corresponding to higher viral RNA concentrations and higher infectiousness [ 2 ]. Some studies reported lower SARS-CoV-2 viral loads in the nasopharynx/oropharynx of asymptomatic patients (children and adults) with shorter viral shedding compared to symptomatic patients [ 3 7 ]. Other studies observed similar viral loads in respiratory tract samples from asymptomatic or pre-symptomatic persons compared to symptomatic patients and long-term virus shedding in asymptomatic patients [ 2 , 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another recent study on 38 samples from 13 COVID-19 patients with known date of symptom onset, 33% of patients seroconverted for IgG between 3rd and 7th day pso [17]. Although, in this regard, some studies didn't report any significant difference among different type of patients (asymptomatic, pre-symptomatic, and symptomatic) [10,12,18], another two analytic studies underlined a major proportion of early responders among hospitalized [6,19] and severe patients [20]. In particular Iyer et al [19] reported that the median time to seroconversion to SARS-CoV-2 RBD was, on average,4 days earlier for ospitalized patients compared with non-hospitalized patients, suggesting an association between antibody kinetics and disease severity.…”
Section: The Antibody Response and Its Kineticsmentioning
confidence: 97%
“…Regarding the kinetics of antibody response, studies have generally observed an increase of both IgG and IgM during the first 3 weeks post-symptoms onset (pso); at 3-4 weeks pso almost all patients presented seroconversion while both antibodies types reach the peak [10]. After the third week, IgM begin to decrease, while IgG remain stable for longer time and sustained levels were detected until 6-7 months so far, even if a great variability was observed among patients [9,[12][13][14][15][16]. However, interestingly, some studies that focused on the analysis of patients' serum starting from first days pso, have reported that most SARS-CoV-2 infected patients mount an early antibody response.…”
Section: The Antibody Response and Its Kineticsmentioning
confidence: 99%
See 1 more Smart Citation